PERLINDUNGAN HUKUM TERHADAP TENAGA KERJA PERHOTELAN KHUSUS KAUM WANITA DI TINJAU MENURUT UNDANG-UNDANG NO. 13 TAHUN 2003 TENTANG KETENAGAKERJAAN - Rina Febriani (Journal of Law ( Jurnal Ilmu Hukum ), 2015)
ABSTRACTSet of problem protection of women energy is one of problem which faced oftentimes if we talk about women energy in indonesian in habitual action much of women which have to work fulfill their life necessity. The action of program safety and health job for importance worker include all of aspect such as include the action right fondation worker, the action of health and safety this case arranged in law number 13 at 2003 about matters pertaining section 86 which the contents arrange about rights worker of law in knowledge section 76 verse 4 of law number 13 at 2003, cabinet of work energy and transmigrant number KEP.224/MEN/2003 about transportation take up and pick up for women worker which have job on night.Transportation which much given by industrialist to women energy which have job on night should to have collateral safety women which have job at enterprise when they have to have shift night and there is transportation facility which take up them to go home until their at home. Institute goverment which handle matters pertaining need to do applicate of law related with health and safety work especially about take up and pick up to women worker which have job on night need to enhance enymore.